O papel da resiliência na redução do desperdício de alimentos: um estudo qualitativo na díade varejo-fornecedor de frutas, legumes e verduras (FLV) - Costa, Flávio Henrique de Oliveira (Universidade Federal de São Carlos, 2019)
Increasingly complex supply chains have become more vulnerable to risks and consequent disruptions of different natures. In the perishable chain, this ends up resulting in increased food waste. To respond effectively to these events, organisations need to develop dynamic capabilities (DCs) and resilience for managing their resources. Considering this opportunity, this thesis aims to explore how the contribution of resilience elements to the reduction of waste from FLVs occurs in the retail-supplier dyad. To this end, a systematic literature review was first carried out (2000-2017) and 143 articles were selected and analysed to gain in-depth knowledge of the elements of resilience and causes of food waste, as well as the relationship between both constructs. Then, empirical research was developed using a multi-case study on four food retail chains focusing on the retail-supplier dyad. Based on the empirical analyses, new causes of waste emerged, namely: unpredictability of competition, store location and consumption aspects. It was also observed that the most recurring causes of waste were rigid standards of appearance and shape, short shelf life, inadequate demand forecasting and consumption aspects. Among these, the most aggravating factor was the short shelf life of products, which reduces the time available for transportation and display, and can become even more critical when difficulties arise with retail demand forecasting. Some aspects of the dyad influence the relationships between elements and causes such as: type of purchase (producers or wholesalers), the place where goods are received (Distribution Centre or store-to-store delivery) and type of demand forecasting (centralized or store-to-store). From the results of the cross cases, as well as the microfoundations of the theory of dynamic capabilities (sensing, seizing and transforming), a model with 24 possible actions was developed to make these FVG chains more resilient and oriented towards reducing food waste. In the theoretical context, this research contributes by exploring the relationship between elements of resilience and causes of waste. In practical terms, identifying elements of resilience enables organisations to take effective action to reduce food waste in this particular chain.
The role of resilience in reducing food waste: a qualitative study in the retailer-supplier dyadic of fruit and vegetables
Keywords: Resiliência; Cadeia de suprimentos; Capacidades dinâmicas; Desperdício de alimentos; Varejo; FLV; Resilience; Supply chain; Dynamic capabilities; Food waste; Retail; FVG; ENGENHARIAS::ENGENHARIA DE PRODUCAO